The Effectiveness of Ethnopedagogy-Based Digital Book Processing in Improving Civics Learning Outcomes in Distance Learning - Novita Majid; Warman Warman (Educational Studies: Conference Series, 2021)
Distance learning in the midst of the current pandemic seems to be a challenge for the creativity of educators to find the right way how to continue to deliver learning materials effectively, the use of technology such as digital books as learning media is one of the appropriate and innovative steps so that the expected goals learning can be achieved. This study aims to improve the learning outcomes of class X SMK Negeri 1 Muargkyu on the subject of National Integration in the Unity in Diversity Frame. This study uses a class action research design. Data were collected through observation, self-assessment, peer-to-peer assessment, journals, interviews, and documentation. There are two data analysis, namely qualitative and quantitative data analysis. The corrective action of learning takes place in 2 cycles consisting of planning, action, observation, and reflection activities. During the learning activities, the students actively participate well. Learning activities that involve students starting from previously doing stimuli through ethnopedagogy-based digital books, observations, value clarification, discussions, compiling reports to evaluations. The results showed that it was successful in improving student learning outcomes of class X SMK Negeri 1 Muarkayu. Improved student learning outcomes (KKM) 90% of the total number of students as a whole.